Visceral Leishmaniasis in a 25-Year-Old Female Kidney Transplant Recipient from a Non-Endemic Region: A Case Report from Romania - Alin Gabriel Mihu; Mariana Patiu; Delia Monica Dima; Daniela Adriana Oatis; Cristina Mihaela Cismaru; Rodica Lighezan; Tudor Rares Olariu (Microorganisms)
Visceral leishmaniasis is a rare parasitic infection in non-endemic regions such as Romania. We report the case of a 25-year-old female kidney transplant recipient from Cluj County, Romania, who developed persistent bicytopenia with anemia and thrombocytopenia. Despite no history of travel outside Cluj County and being the only organ recipient from the same donor to experience signs and symptoms, she was diagnosed with visceral leishmaniasis. The second bone marrow aspirate performed revealed Leishmania amastigotes. She was quickly sent to Victor Babes Infectious Disease Hospital in Bucharest for additional tests and treatment. The kidney function of the patient was maintained. This case highlights the importance of considering leishmaniasis in immunosuppressed patients presenting with unexplained cytopenia, even in non-endemic regions. This is the first documented case of visceral leishmaniasis in a kidney transplant recipient in Romania. The present report could serve as a foundation for future educational programs targeted toward informing both healthcare providers and patients about the risks, diagnosis, and management of leishmaniasis in immunosuppressed individuals in non-endemic regions.